IMPACTO DE LA MOTIVACIÓN Y EL LIDERAZGO EN EL RENDIMIENTO LABORAL EN UNA EMPRESA DE SERVICIOS DE LIMA METROPOLITANA - Tito Huamaní, Pedro Leonardo (2013)
They conducted a study to determine whether the motivation and leadership are related to job performance in a service company of Lima. It was felt that the independent variables were the motivation and leadership. The dependent variable was job performance. For the measurement of the relevant variables, we applied the Motivation Questionnaire Sudarsky and Cleves (2000) that measures three types of motivation (achievement motivation, affiliation motivation and power motivation). To measure was applied leadership variable measuring instrument Mellado Climate and Leadership (2005), which assesses the same three types of leadership (Executive Leadership, Educational Leadership and Administrative Leadership. Measuring work performance was applied Occupational Performance Scale (JS . Job Survey) of Bryman and Cramer (1997) assesses the same aspects of ability, quality and productivity. population consisted of 296 employees in 10 branches of Lima Lima Metropolitana. Sampling was applied with allocation probabilistic professional. The sample consisted of 167 workers. The general hypothesis proposed that there was a significant relationship between motivation and leadership with job performance. To test the hypotheses we assumed a descriptive correlational design to apply the product - moment correlation of Pearson at a significance level of p: 0.05. We found significant positive correlations between motivation in its three forms (achievement motivation, affiliation and power) with job performance and leadership among the job performance of employees. The results proved that the motivation and leadership are positively related to job performance. This implies that the increased motivation levels correspondingly increases work performance. Also, with increasing levels of leadership increases performance of workers. Thus the hypotheses were tested. The study found the theoretical assumptions about the influence of motivation and leadership on the performance of the worker. The results are consistent with other research on the subject which corroborates our findings. Conclusions were raised and recommendations.